PENERAPAN MODEL PEMBELAJARAN DIRECT INSTRUCTION BERBANTUAN LABORATORIUM VIRTUAL DALAM PEMBELAJARAN MATERI MOMENTUM DAN IMPULS - Sakina, Syarifah Fachrunisa; Djudin, Tomo; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe research goal is to know the effectivity of the implementation of direct instruction model by using the virtual laboratory to the learning result on momentum and impulse topic of 10th grade student of SMA Negeri 3 Pontianak. The form of this research is experimental research and the method is quasi experimental design with the nonequivalent control group design. This research was involved by 24 students from 10th grade MIPA 4 and 18 students from 10th grade MIPA1 with the intact group technique. The research instrument is the test result that consists from 10 multiple choice questions and 2 essays. The result analysis from pretest and posttest showed that there was significant change of the learning result that was proven by 25,85% changes on the control class and 50.8% on the experiment class. There was a significant learning result between the implementation of direct instruction with the virtual laboratory and without virtual laboratory. The implementation of direct instruction model by utilizing the virtual laboratory is effective to improve the learning result on momentum and impulse topic with score of 3,25 effect size which is considered as high. Â Keyword: Implementation, direct instruction, virtual laboratory, learningresult, momentum and impulse.